2017
DOI: 10.1155/2017/7597596
|View full text |Cite
|
Sign up to set email alerts
|

Radix Bupleuri: A Review of Traditional Uses, Botany, Phytochemistry, Pharmacology, and Toxicology

Abstract: Radix Bupleuri (Chaihu) has been used as a traditional medicine for more than 2000 years in China, Japan, Korea, and other Asian countries. Phytochemical studies demonstrated that this plant contains essential oils, triterpenoid saponins, polyacetylenes, flavonoids, lignans, fatty acids, and sterols. Crude extracts and pure compounds isolated from Radix Bupleuri exhibited various biological activities, such as anti-inflammatory, anticancer, antipyretic, antimicrobial, antiviral, hepatoprotective, neuroprotecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
131
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(133 citation statements)
references
References 106 publications
0
131
0
2
Order By: Relevance
“…Cholestatic liver injury has been reported in the use of OA‐type triterpenoid containing herbal mixtures . Table lists a few examples, Saikosaponins are oleanane‐type triterpenoids and are the major bioactive compounds isolated from Radix Bupleuri .…”
Section: High Doses and Long‐term Use Of Oa And/or Oa Derivatives Promentioning
confidence: 99%
See 3 more Smart Citations
“…Cholestatic liver injury has been reported in the use of OA‐type triterpenoid containing herbal mixtures . Table lists a few examples, Saikosaponins are oleanane‐type triterpenoids and are the major bioactive compounds isolated from Radix Bupleuri .…”
Section: High Doses and Long‐term Use Of Oa And/or Oa Derivatives Promentioning
confidence: 99%
“…Table lists a few examples, Saikosaponins are oleanane‐type triterpenoids and are the major bioactive compounds isolated from Radix Bupleuri . A systemic review of Saikosaponins isolated from Radix Bupleuri showed anti‐inflammatory, antitumor and hepatoprotective effects, similar to OA . Saikosaponin d was effective in protecting against acetaminophen‐induced liver injury .…”
Section: High Doses and Long‐term Use Of Oa And/or Oa Derivatives Promentioning
confidence: 99%
See 2 more Smart Citations
“…or Bupleurum scorzonerifolium Willd. Saikosaponins are the most effective ingredients of BR. Licorice is a common TCM that is derived from the root and rhizome of Glycyrrhiza uralensis Fisch .…”
Section: Introductionmentioning
confidence: 99%